Substance use initiation, particularly alcohol, in drug-naive adolescents: possible predictors and consequences from a large cohort naturalistic study - Ivanov, Iliyan; Parvaz, Muhammad A.; Velthorst, Eva; Shaik, Riaz B.; Sandin, Sven; Gan, Gabriela; Spechler, Philip; Albaugh, Matthew; Chaarani, Bader; Mackey, Scott; Banaschewski, Tobias; Bokde, Arun L. W.; et al. (Journal of the American Academy of Child and Adolescent Psychiatry, 2021)
Objective - It is unclear whether deviations in brain and behavioral development, which may underpin elevated substance use during adolescence, are predispositions for or consequences of substance use initiation. Here, we examine behavioral and neuroimaging indices at early and mid-adolescence in drug-naive youths to identify possible predisposing factors for substance use initiation and its possible consequences. - Method - Among 304 drug-naive adolescents at baseline (age 14 years) from the IMAGEN dataset, 83 stayed drug-naive, 133 used alcohol on 1 to 9 occasions, 42 on 10 to 19 occasions, 27 on 20 to 39 occasions, and 19 on >40 occasions at follow-up (age 16 years). Baseline measures included brain activation during the Monetary Incentive Delay task. Data at both baseline and follow-up included measures of trait impulsivity and delay discounting. - Results - From baseline to follow-up, impulsivity decreased in the 0 and 1- to 9-occasions groups (p < .004), did not change in the 10- to 19-occasions and 20- to 29-occasions groups (p > .294), and uncharacteristically increased in the >40-occasions group (p = .046). Furthermore, blunted medial orbitofrontal cortex activation during reward outcome at baseline significantly predicted higher alcohol use frequency at follow-up, above and beyond behavioral and clinical variables (p = .008). - Conclusion - These results suggest that the transition from no use to frequent drinking in early to mid-adolescence may disrupt normative developmental changes in behavioral control. In addition, blunted activity of the medial orbitofrontal cortex during reward outcome may underscore a predisposition toward the development of more severe alcohol use in adolescents. This distinction is clinically important, as it informs early intervention efforts in preventing the onset of substance use disorder in adolescents.
Gesehen am 06.10.2021